PENGARUH KEPEMIMPINAN KEPALA SEKOLAH DAN BUDAYA ORGANISASI TERHADAP KINERJA MENGAJAR GURU DI YAYASAN PONDOK KARYA PEMBANGUNAN (PKP) JIS, KELURAHAN KELAPA DUA WETAN CIRACAS JAKARTA TIMUR - Wawan Ridwan (Akrab Juara : Jurnal Ilmu-ilmu Sosial, 2019)
The purpose of this study is in an effort to search for data, facts, and information obtained both from the field and from existing documents, about the leadership of the school principal, organizational culture and teacher teaching performance. The method used in this research is quantitative, this method is commonly used as one of the research models, this method fulfills the scientific / scientific rules that are concrete / empirical, objective, measurable, rational and systematic, this method is called quantitative because the research data is in the form of numbers and the analysis uses statistics. The sample used uses the Slovin formula from 112 populations that were sampled as 53 people. Based on the results of the study there is an influence between the principal's leadership (X1) and teacher's teaching performance (X3) which is described by the equation X3 = 37.612 = 0.685X1 meaning it can be used as a tool to explain and draw conclusions about the influence between the principal's leadership (X1) and performance teaching teachers (X3), every increase of one unit of principal leadership will increase 0.685 units of teacher teaching performance with a constant of 37,612.